Efektifitas kegiatan pelatihan pembuatan ovitrap DBD pada santri Pondok Pesantren Al Falah Banjarbaru - Tien Zubaidah; Juanda Juanda; Isnawati Isnawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The negative impact of the insecticides usage triggers the development of new methods other than insecticides, one f them is ovitrap tools (mosquito egg traps). The use of ovitrap as part of dengue prevention efforts has proven to be easy, cheap, safe for health and environmentally friendly. Ovitrap is effective in reducing mosquito populations. The purpose of the activity is to analyze the knowledge, attitudes and actions of students in the use of ovitrap as an effort to control Aedes sp mosquito larvae after the implementation of health counseling activities and demonstrations of making Ovitrap. All students at Pondok Pesantren Al Falah Putera became the population. As many as 96 students who were willing and involved in this activity became the research sample. McNemar test showed significant results on knowledge (0.018), attitude (0.033) and action (0.00). The making andthe use of Ovitrap socialization still needs to be sought in order to increase the Santri knowlwege.. It is hoped that this activity can be implemented every year as an effort to reduce the risk of dengue fever in Banjarbaru Cit